2019
DOI: 10.1016/j.ijid.2019.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Mayaro as a Caribbean traveler: Evidence for multiple introductions and transmission of the virus into Haiti

Abstract: Mayaro virus (MAYV) is a mosquito-transmitted alphavirus that is being recognized with increasing frequency in South America. As part of ongoing surveillance of a school cohort in Haiti, we identified MAYV infections in 5 children across a 7-month time span, at two different school campuses. All had a history of fever, and three had headaches; none complained of arthralgias. On analysis of whole genome sequence data, three strains were genotype D, and two were genotype L; phylogenetic and molecular clock analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 15 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…As expected, our analysis suggests a Caribbean origin for the Manatee County isolate due to movements of DENV4 into Florida from Haiti and, preceding that, into Haiti from Puerto Rico. These results agree with previous findings depicting the Caribbean as a hot spot for arboviral spread in the Americas (18)(19)(20). Diversifying selective pressure in the NS2A gene and the 2K peptide ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, our analysis suggests a Caribbean origin for the Manatee County isolate due to movements of DENV4 into Florida from Haiti and, preceding that, into Haiti from Puerto Rico. These results agree with previous findings depicting the Caribbean as a hot spot for arboviral spread in the Americas (18)(19)(20). Diversifying selective pressure in the NS2A gene and the 2K peptide ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed an epidemiological link between Zika outbreaks in Haiti and the southwest region of the Dominincan Republic. This connection likely extends to other mosquito-borne viruses such as Mayaro virus and West Nile virus, which have been reported in Haiti [58][59][60] . The former can be transmitted by Aedes mosquitoes 14,[61][62][63] , and the latter has been isolated from zoonotic reservoirs in the Dominican Republic 64 .…”
Section: Discussionmentioning
confidence: 53%
“…The analysis showed that the MAYV isolate diverged about 100 years ago from the 2010 Venezuelan isolates, with the time of the MRCA (tMRCA) dating back to 1914 (with a 95% high posterior density (HPD) interval of 1883-1936). The tMRCA for the 2016 MAYV isolate and the most closely related MAYV isolates to this isolate (DQ001069, isolated in 1999 in French Guiana, and MK837006 and MK837007, isolated in 2014 in Haiti 29 ) was more recent, dating back to 1980 (with a 95% HPD interval of 1971-1988). The tMRCA for subsequent divergence of the lineages leading to the French Guiana strain and the Haitian strains dated to 1996.…”
Section: Resultsmentioning
confidence: 96%